2015
DOI: 10.11604/pamj.2015.20.50.5251
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminthic infections among elementary students of Babile town, eastern Ethiopia

Abstract: IntroductionIntestinal helminthic infections are important public health problems in developing countries. In Ethiopia, intestinal parasitic infections are highly prevalent because of low living standards and poor environmental sanitation. There are several areas in Ethiopia from which epidemiological information is lacking including Babile town. The aim of this study was to determine the prevalence of intestinal helminthic infection among students of Babile town.MethodsA cross sectional study was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 17 publications
7
25
8
1
Order By: Relevance
“…This was almost comparable with the study done in Were-abay 12.22% [16] and Babile town 13.8% [17]. But the result of this study was much lower than the findings reported in Adwa town 69% [28], Lumame town 54%) [27], Zegie Peninsula 69.1% [29] and in northern Gondar 66.7% [30].…”
Section: Discussionsupporting
confidence: 82%
“…This was almost comparable with the study done in Were-abay 12.22% [16] and Babile town 13.8% [17]. But the result of this study was much lower than the findings reported in Adwa town 69% [28], Lumame town 54%) [27], Zegie Peninsula 69.1% [29] and in northern Gondar 66.7% [30].…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of S. mansoni was lower than those studies conducted in Zegie and Azezo and reported 29.9% and 43.5% respectively (21,26). The prevalence of hookworm in this work was greater than the result of a study conducted in Babile (0.3%) (27) and lower than that of Bahir dar (22.8%) (24) and Debre Elias (71.2%) (5). This could be related to shoe waring habits, distribution of the parasite in the community and differences in geographical area and population awareness about parasite transmision.…”
Section: Prevalence and Associated Risk Factors Of Intestinal Parasitcontrasting
confidence: 81%
“…10 Similarly, a study by Tefera and others in eastern Ethiopia showed that while the prevalence of STHs was less than 0.5%, the prevalence of H. nana was 13% in elementary school children receiving regular deworming treatment. 11 Hymenolepis nana has been associated with diarrhea and other gastrointestinal symptoms among children. [12][13][14][15] In Mexico and Cuba, children with H. nana infection commonly had abdominal pain, anorexia, irritability, and diarrhea.…”
Section: Discussionmentioning
confidence: 99%